2018
DOI: 10.3892/ol.2018.9075
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP24 regulates cell ability and apoptosis ofcolorectal cancer cells via the regulation of P53

Abstract: Colorectal cancer is a human malignancy ranked the third highest of the global incidence of malignant tumors. Rho GTPase-activating proteins (RHOGAPs) were identified functional in several processes of tumors. In the present study, through reverse transcription-quantitative PCR (RT-qPCR) and western blot analysis, expression of Rho GTPase-activating protein 24 (ARHGAP24) and p53 was measured in colorectal cancer tissues, which was lower than that in adjacent normal tissues, revealing that ARHGAP24 may be impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…In literature there was no clear association between the tumor recurrence and the occurrence of the p21ras protein expression, which is compliant with the observations by other authors [28][29][30]. In our own study we have also found that the level of p21 is not related to cancer recurrence.…”
Section: Discussionsupporting
confidence: 91%
“…In literature there was no clear association between the tumor recurrence and the occurrence of the p21ras protein expression, which is compliant with the observations by other authors [28][29][30]. In our own study we have also found that the level of p21 is not related to cancer recurrence.…”
Section: Discussionsupporting
confidence: 91%
“…The ARHGAP10 gene was found to regulate actin cytoskeleton remodeling, cell proliferation, and cell differentiation. The ARHGAP10 interacts with α-tubulin and it is involved in cell-cell adhesion processes and consequently could promote cell migration [58][59][60][61][62]. In our study, overexpression of ARHGAP10 was associated with lower meat quality index.…”
Section: Expression Association Analysis For the Meat Quality Indexsupporting
confidence: 52%
“…The ARHGAP10 gene was found to regulate actin cytoskeleton remodeling, cell proliferation, and cell differentiation. The ARHGAP10 interacts with α-tubulin and it is involved in cell-cell adhesion processes and consequently could promote cell migration [12][13][14][15][16]. In our study, overexpression of ARHGAP10 was associated with lower meat quality index.…”
Section: Gene Expression Association Analysis For the Meat Quality Indexsupporting
confidence: 52%